A comparative study of sexual behavior, dysfunction, satisfaction, relationship, and sexual quality of life amongst treatment-naïve and abstinent men (buprenorphine-maintained) with Opioid (heroin) dependence syndrome - Mahadev Singh Sen; Ankita Chattopadhyay; Nishtha Chawla; Ragul Ganesh; Suraj Verma; Siddharth Sarkar; Atul Ambekar (Indian Journal of Psychiatry)
Background: Association between opioid use and sexual functioning is well-known. However, data evaluating the influence of treatment on different aspects of sexuality are lacking. Aim: To compare sexual behavior, functioning, relationship, satisfaction, and sexual quality of life (sQoL) among treatment naïve patients (GROUP-I) with Opioid (heroin) dependence syndrome (ODS-H) with those maintained on buprenorphine (GROUP-II). Methods: Married adult males diagnosed with ODS-H, currently sexually active, and living with their partner were recruited. They were assessed for their sexual practices and high-risk sexual behavior (HRSB) through a semi-structured questionnaire and sexual functioning, relationships, satisfaction, and sQoL through structured questionnaires. Results: A total of 112 individuals (GROUP-I: 63; GROUP-II: 49) were recruited from the outpatient settings. Mean age and employment in GROUP-II were higher (p < 0.05) than in GROUP-I (37 vs 32 years; 94% vs 70%, respectively). Other sociodemographic variables and the age of onset of heroin use were comparable. The current practice of HRSB (e.g., engaging in casual partner sex, sex with commercial sex workers, and sex under intoxication) was higher in GROUP-I while almost no differences were seen in lifetime HRSB. The frequency of erectile dysfunction and premature ejaculation in the two groups were: 78% vs 39% (p < 0.001), and 30% vs 6% (p = 0.001), respectively. GROUP-II had significantly higher scores in all the scales (p < 0.05) as compared to GROUP-I, indicating better sexual satisfaction, quality of life, and sexual relationship. Conclusion: Heroin use is associated with HRSB, poorer sexual functioning, overall satisfaction, and sQoL. Maintenance of Buprenorphine helps with improvement in all these parameters. Comprehensive management for substance use should target sexual problems as well.